Kajian Balaghah Dalam Al-Qur’an Surat Luqman - Muhammad Zaky Sya’bani (Institut Agama Islam Negeri Metro, 2019)
The science of Balaghah is in fact not only examined by text. Long before that, it turns out that in the Qur'an there are the beauty of languages that the Arab poet could not have matched though. More interesting, the beauty and style of language in the surah Luqman when studied with the science of Balaghah contains three important elements in human life. Namely, the education of Aqidah, sharia and morality. In this study Balaghah science is examined specifically and in depth by the author with ilmu Ma'ani. In the science of Ma'ani, the authors deepen the study of Insha Kalam discussing Amr Balaghi. And at the end of this study the author found 2 out of 9 kinds of Balaghi Amr, both of which have the meaning of al-Irsyad and at-Tahdid. Amr has the meaning of al-Irsyad found in verses 12, 14, 15, 17, 19, 21. While Amr has the meaning of at-Tahdid in verses 7 and 33. And all the meanings of al-Irsyad and at-Tahdid this can assert the meaning of the content of the surah Luqman itself. So in the end, it can help in human life. At the same time, it confirms that the Qur'an is a miracle for human understand.